Crianças com dificuldades em resolução de problemas matemáticos : avaliação de um programa de intervenção - Moura, Graziella Ribeiro Soares (Universidade Federal de São Carlos, 2007)
The comprehension of written texts continues being one of the most difficult academic practices for students of Basic Education. If comprehending a written material in linguistic terms brings out difficulties for some students, a text written in mathematical language can be even more difficult, because besides the mother language understanding, mathematical concepts are also needed. A lot of research has been done to try to find better ways to help children understand what was asked in mathematical problem-questions. However, there is a lot to be done to understand the difficulties and processes of problem resolution and about basic conceptual comprehension present in mathematical problems instructions. In this sense, the purpose of the present study was to elaborate, apply and evaluate an intervention program performed with children in the fourth year of Elementary School who showed difficulties comprehending and solving mathematical problems, and maximize their cognitive capacity. The methodology chosen was the experimental delineation of comparison between groups, an experimental and a control group. The study consisted of a pretest, an intervention program, a post-test and a delayed post-test. The pretest evaluated the children s performance in resolving arithmetical problems. Next, the teaching program was used with students who showed performance under 40% right in problems. This aimed to develop, in the students, enough knowledge to increase their resolution capacity of mathematical problems. That program sought to teach students to read mathematical problems instructions and find the most appropriate mathematical representation to solve the question. For this, it was necessary to teach the arithmetical operations concepts, since one of the children s difficulties was connected with understanding the meaning of each operation (addition, subtraction, multiplication and division) and its symbolic representation. The post-test and delayed posttest results for the experimental group were superior to the pretest results for the experimental and control groups, indicating an improvement in performance for the students who took part in the program. Those data showed that the intervention utilized was efficient, increasing the cognitive capacity necessary to the task of resolving arithmetical problems, which basically consists of comprehending written instructions and representing them mathematically.
Keywords: Educação especial métodos de ensino; Dificuldade de aprendizagem; Ensino aprendizagem de matemática; Resolução de problemas; Education; Special Education. Mathematical Education; Arithmetical problems resolution; Mathematical texts comprehension; Learning disabilities; Intervention Program; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL